Poluição industrial da Bacia do Rio Gramame e conflito socioambiental: análise da complexidade a partir dos atores, impactos e perspectivas - Nunes, Edilon Mendes (2012)
This is a case study of Political Ecology, wherein we deal with the analysis of the Social Environmental Conflict of industrial pollution in the Basin of Rio Gramame, in the community of Mumbaba de Baixo. Although, this conflict began in the decade of 1960, it wasn t until recently that it has been recognized. As we have sought to understand the complexities of this study, we draw a methodological road of analysis from the conflict to each part of which it is comprised. In this way, we identify all those involved, their actions, articulations, powers, and their influence on the conflict. From a Social-anthropological methodology, we utilize the participant s observations, with the "snowball" technique, as well as semi-structured interviews, mental models, analysis of perceptions and photographic records. We did this in order to map the conflict and analyze the form of treatment that it was given, the mediation, as well as the perspectives of resolution to the problem of the conflict that, although it is now clear, and it s watched closely, still manages to remain hidden. All those that are involved, are not well versed in their articulation, and the majority of them do not follow their script as defined by legislation, which commits the perspectives of resolution, where as a result, the situation is only perpetuated. However, the State Department (prosecuting counsel) has found a conflict mediator by lawful means, keeping in mind that the fact of this situation is part of a much bigger conflict. This work becomes prominent by bringing to the surface all of the voices that go unheard, and by that, it is in itself a provocative work. The community of Mumbaba, now fits into a much larger political picture, where participation and articulation seek more information from everyone involved, well beyond the act of signing and the consolidation of partnerships. As far as everyone else involved, it falls on the act of rendering it effective, as well as their rights, and a process of a Social Environmental sensitizing. In conclusion, it is a matter of Environmental Justice, where not only an assembly of humans is affected, but a whole ecosystem.